Towards the Amplification of Children’s Rights within Olympic Discourses - Byrne, Seamus (Eracle. Journal of Sport and Social Sciences, 2024)
The intersection of Mega-Sport Events (MSEs) and human rights has given rise to considerable academic commentary over the last number of years. However, within this literature, the treatment of, and engagement with, children’s rights law, has been comparably negligible in scope and depth. This has been especially true in relation to how the Olympic Games affect children and young people, and their rights. Against this backdrop, this paper argues that the effect of this marginal treatment has resulted in the peripheralization of important children’s rights standards from Olympic discourses. By examining the extant literature on the Olympics and children and young people, in conjunction with an examination of the Concluding Observations and General Comments of the UN Committee on the Rights of the Child, it argues that the effects of the Olympics on children and young people must now be considered as a distinct children’s rights issue. Building on this, and in support of the overarching claim that children’s rights must be amplified within Olympic discourses, it further contends that the International Olympic Committee (IOC) must also foreground respect for children’s rights within their existing legal and contractual frameworks.